The Correlation Analysis Between Salary Gap and Enterprise Innovation Efficiency Based on the Entrepreneur Psychology - Pan, Xingchen; Wan, Xiangyu; Wang, Haoran; Li, Yingji (Frontiers in Psychology, 2020)
Under the analysis of the psychological level of entrepreneurs, the study focuses on discussing the relationship between the salary gap and enterprise innovation efficiency. It provides a reference basis for promoting employee innovation activities and improving the market competitiveness of enterprises. First, the role of entrepreneur psychology in decision-making is explained theoretically. Based on this, the relationship between the salary gap of employees and enterprise innovation is analyzed from a theoretical perspective. In the empirical analysis, this paper selects the data of China's A-share manufacturing listed enterprises from 2012 to 2016 as the research sample. The explanatory variables are the salary of senior management, the salary of the ordinary employee and salary gap. The explained variable is enterprise innovation efficiency. By constructing an econometric model, a multiple regression model is used to empirically analyze the correlation between the salary gap and innovation efficiency. The regression coefficients between monetary salary and equity salary of senior managers and enterprise innovation performance are 5.545 and 1.003, respectively. The regression coefficient between the salary of the ordinary employee and enterprise innovation efficiency is 8.357. The regression coefficient between the internal salary gap of the senior management team and the enterprise innovation efficiency is 3.552, both of which show a significant positive correlation at the 1% level. The regression coefficient between the salary gap between senior managers and ordinary employees and the enterprise innovation performance is -3.032, which is significantly negatively correlated at the 5% level. The internal salary gap of the senior management team has a significant positive effect on enterprise innovation efficiency. The salary gap between senior managers and ordinary employees has a negative effect on enterprise innovation efficiency. Enterprises should optimize the salary structure from two levels of senior managers and ordinary employees, to stimulate the work enthusiasm of employees at all levels, and promote enterprise innovation.